Outcome predictors of autologous hematopoietic stem cell transplantation in children with relapsed and refractory Hodgkin lymphoma: Single‐center experience in a lower‐middle‐income country. (4th July 2019) - Abdalla, Amr; Hammad, Mahmoud; Hafez, Hanafy; Zaghloul, Mohamed Saad; Taha, Hala; El‐Hennawy, Gihan; El‐Wakeel, Madeeha; Khaled, Mohamed; Mohamed, Yasmin; El‐Haddad, Alaa
Abstract: Background: Children and adolescents with HL have excellent long‐term survival exceeding 95% after combined modality treatment. However, about 20% will either relapse or have PRF. Salvage HDCT followed by AHSCT is considered to be the preferential treatment. Objective: To describe the outcome (OS and EFS) and prognostic factors in pediatric patients with relapsed or refractory HL (r/rHL) who underwent AHSCT. Methods: We retrospectively included 43 pediatric patients with r/rHL who underwent AHSCT from July 1, 2007, till December 31, 2016, at the Children's Cancer Hospital of Egypt. MAC regimen given was CMV. Results: Of the whole cohort, 88.4% of patients achieved CR, while 11.6% had a positive PET scan prior to transplantation. The 3‐year OS and EFS were 85% and 70.6%, respectively. The 3‐year OS for patients > 10 years was 94% versus 65.5% for patients 10 years of age or younger ( P  = 0.046). There is strong tendency toward better 3‐year OS for patients with negative PET scan as compared to those with positive PET scan before AHSCT, 89.4% vs 60%, respectively ( P  = 0.059). This tendency is also applicable when looking at the 3‐year EFS for the two groups, 78.3% vs 40%, respectively ( P  = 0.069). Conclusion: Poor predictors of OS were younger age and positive PET scan before AHSCT. The latter, along with single modality treatment before AHSCT, were poor predictors of EFS.